Keeping Faith: Faith-Based Organizations as Urban Migration Infrastructures for Illegalized Migrants in Rotterdam - Vasileiadi, Carola (2024)
In recent years, scholarship on arrival infrastructures has refocused attention to the importance of the local level as the main site where the social in- and exclusion of newcomers is negotiated. However, this focus on newcomers has relatively overlooked the plight of long-term residents like illegalized migrants (IMs) who are “stranded” or “stuck” in their cities of residence. Faith-based organizations (FBOs) have historically functioned as sanctuaries that provide services and resources to IMs. Based on ethnographic research at the Pauluskerk in Rotterdam, we argue that the processes whereby FBOs are able to negotiate and contest the in- and exclusion of IMs in hostile environments can better be grasped by conceptualizing them as “urban migration infrastructures.” By introducing this term, we open up the debate about the relative orientation of migration infrastructures beyond arrival and emphasize their relational and spatial embeddedness within broader “infrastructural fields.” On the one hand, our analysis demonstrates that FBOs mediate access to material resources via providing shelter, healthcare and possibilities for volunteering. On the other hand, we show that FBOs provide immaterial resources by stimulating a sense of belonging, assisting IMs legally and engaging in political advocacy. Extending the lessons learned from this case study, we argue that FBOs need to constantly navigate the symbolic space between in/formality when engaging in infrastructuring work towards IMs. Our findings simultaneously indicate that the unique role that FBOs play as “safe havens” in hostile political environments comes under pressure as local governments incorporate their efforts into local reception policies.